2006
DOI: 10.1007/s10534-006-9016-0
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium and mercury cause an oxidative stress-induced endothelial dysfunction

Abstract: We investigated the ability of cadmium and mercury ions to cause endothelial dysfunction in bovine pulmonary artery endothelial cell monolayers. Exposure of monolayers for 48 h to metal concentrations greater than 3-5 microM produced profound cytotoxicity (increased lactate dehydrogenase leakage), a permeability barrier failure, depletion of glutathione and ATP and almost complete inhibition of the activity of key thiol enzymes, glucose-6-phosphate dehydrogenase (G6PDH) and glyceraldehyde-3-phosphate dehydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 26 publications
1
56
0
Order By: Relevance
“…In line with that, Elia et al (2003) also found that moderate doses of mercury were able to increase GST and GPx activities in Ictalurus melas, whereas high concentrations inhibited those enzymes. Similarly, Wolf and Baynes (2007) have described that in mammals high concentrations of mercury ([3-5 lM) induced GSH depletion and inhibition of thiol enzymes activity, whereas low concentrations (1-2 lM) increased those parameters.…”
Section: Oxidative Stress Responses and Association With Mercury Accumentioning
confidence: 82%
“…In line with that, Elia et al (2003) also found that moderate doses of mercury were able to increase GST and GPx activities in Ictalurus melas, whereas high concentrations inhibited those enzymes. Similarly, Wolf and Baynes (2007) have described that in mammals high concentrations of mercury ([3-5 lM) induced GSH depletion and inhibition of thiol enzymes activity, whereas low concentrations (1-2 lM) increased those parameters.…”
Section: Oxidative Stress Responses and Association With Mercury Accumentioning
confidence: 82%
“…Kim and Sharma (2004) found, that initial action of mercury on macrophages is going through the mobilization of Ca 2+ ions and resulting in increased reactive oxygen species (ROS) production leading to apoptotic and necrotic changes in macrophages. Mercury increased free radical production and oxidative stress in animal and human studies (Wiggers et al, 2008;Wolf & Baynes, 2007). On the contrary, low doses of Hg (2 -4 µM) stimulated NO production in cells of rats (Ellis et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Despite lack of correlation between BCd and fibrin D-dimer level, it cannot be excluded that fibrinolysis-induced endothelial damage may be disturbed by cadmium. It is suggested that the mechanism of fibrinolytic system activation by cadmium may result from multidirectional effect of this metal, including interactions with essential elements, disturbances of red-ox processes or increased endothelium permeability [46,47]. In plasma of the women with endometrial cancer, an increase of t-PA level was detected, which did not occur in the women with myoma.…”
Section: Discussionmentioning
confidence: 99%